Softwarová podpora plánování projektů - Škorpík, Vojtěch (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce se zabývá softwarovou podporou v plánování projektů a vysvětluje základní pojmy týkající se této oblasti. V praktické části jsou řešeny časové plány ve specializovaných programech na příkladu rekonstrukce pomocného skladu. Cílem této práce je popsat softwarové produkty pro projektové řízení a porovnat je na základě určených kritérií.

This bachelor’s thesis is dealing with software support of project planning and defines basic terms related to this subject. Empirical part focuses on time schedules in specialised programmes. For this purpose, reconstruction of a warehouse was used as an example. The aim of this thesis is to describe software products used for the project management and compare them according to specific criteria.
Software Support of Project Planning
Keywords: Projekt; projektové řízení; plán projektu; Ganttův diagram; Microsoft Project; Easy Project; ProjectLibre; Project; the project management; the plan project; the Gantt´s diagram; Microsoft Project; Easy Project; ProjectLibre